Mechanistic Study of Induced Oxidation of Formic Acid in Presence of Sodium Arsenate - Zaheer, Ahmed; Ahmed Farooqui, Mazahar; Mohammad Arif, Pathan (Asian Journal of Chemistry, 2010)
The mechanistic proposal fo induced oxidation by using As(III) as inductor and fonnic acid as acceptor were investigated. A probable mechanism has been suggested on the basis of induction factor (I.F.). It is observed that Mn5+ acts as reactive intermediate and induces the oxidation of formic acid through anhydride formation.